(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Tactics of treatment of traumatic optic neuropathy (TON) is controversial. The use of high doses of corticosteroids is considered the standard of care at the tone in many countries. However, there are still many questions related to the severe side effects of this therapy and the inability to use it in the most optimal period (first 48 hours), when the patient is usually burdened with concomitant lesions. The aim was to discover of treatment of traumatic optic neuropathy with high doses of corticosteroids. Material and methods. There were treated three patients with TON. Results. The study of medicinal properties of high-dose corticosteroids showed their positive influence in TON. There were detected increasing of visual function and normalization of eye’s fundus in the background of pulse therapy with Methylprednisolone. The effect was unstable. Atrophic changes in the optic nerve continued development on the affected side as well as on the opposite side of proving inadequacy of the proposed scheme. Conclusion. So, high doses of corticosteroids contribute in improving the treatment of TON.